Effect of adding Aureomycin® for anaplasmosis control or Rumensin® to mineral supplements on summer beef cowherd performance - Llewellyn, Donald A.; Marston, T.T.; Breiner, Ryan M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two hundred forty-six commercial Angusbased cows were used to determine the effect of adding Aureomycin® for anaplasmosis control or Rumensin® to mineral supplements on summer beef cowherd performance. Cow/calf pairs were randomly allotted to summer native-pasture groups by treatment, and were fed an industry-standard mineral/trace mineral supplement for the duration of the trial. The study had three treatments: (1) control mineral supplement with no medication added, (2) the same base supplement with the addition of Aureomycin® (0.5 mg/lb cow body weight daily), and (3) the base supplement with the addition of Rumensin® (200 mg/cow daily). Feed additives were blended into the mineral mix to provide the targeted daily consumption. Treatments were initiated May 6 and maintained through October 6. Mineral intake was similar among treatments. Cow and calf weight gains were similar among treatments during the first 32 days of the study. By the trial end, there were no significant differences in cow body condition score gains and pregnancy rates. Total calf gains for the duration of the trial were similar for groups supplemented with Aureomycin®, and Rumensin®, and both were greater than for control calves (21 and 18 lb greater, respectively). Overall herd health was enhanced by feeding Aureomycin ® when compared with control or Rumensin ®. Foot rot was the main health concern in this trial, and the addition of Aureomycin ® to mineral supplements reduced foot rot.
Keywords: Beef; Aureomycin®; Rumensin®; anaplasmosis; Performance